Motion planning for efficient and safe module transportation in modular integrated construction. (17th March 2022) - Zheng, Zhenjie; Pan, Mi; Yang, Yi; Pan, Wei
Abstract: Modular integrated construction (MiC) is the most advanced construction method that involves off‐site manufacturing, factory‐to‐site transportation, and on‐site assembly of free‐standing integrated modules. Despite the growing interest in the manufacturability of MiC, little research is available on the passing ability issues where efficient and safe transportation of modules is critical to the project's success. This paper proposes (1) a novel computational method for formulating and solving the module's horizontal passing ability with road constraints as a motion planning problem and (2) a new index to assess the path performance in critical scenarios. The newly developed Truck‐Parallelized Hybrid A Star (TP‐Hybrid A*) has novelties in collision checking, cost function formulation, and parallel computing on different vehicle dimensions. The effectiveness of the developed algorithm was experimentally verified to be superior to the rapid random tree in computation time and path performance and further demonstrated by applying it to a real‐life MiC project. The new index can serve as a useful tool for decision‐making in module dimension design and transportation planning of MiC projects when tackling the module's horizontal passing ability issues.